2005
DOI: 10.1159/000091326
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Interleukin-5 Antibody Therapy in Eosinophilic Diseases

Abstract: Eosinophilia in atopic diseases and hypereosinophilic syndrome is often associated with a high expression of interleukin-5 (IL-5). IL-5 plays an important role in regulating the production, differentiation, recruitment, activation, and survival of eosinophils. Therefore, neutralizing IL-5 with an antibody is a promising therapeutic strategy in eosinophilic diseases. In patients with hypereosinophilic syndrome and eosinophilic esophagitis, anti-IL-5 antibody therapy resulted in an improvement of symptoms. In pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 123 publications
1
22
0
3
Order By: Relevance
“…This finding indicates that eosinophils play a critical role in the airway remodeling in asthma. In addition, recently, anti-IL-5 mAb was shown to be beneficial in patients with hypereosinophilic syndrome [42, 43] and those with eosinophilic esophagitis [44, 45], re-affirming that the eosinophil represents a very important target cell for therapeutic intervention of diseases characterized by eosinophilia. …”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates that eosinophils play a critical role in the airway remodeling in asthma. In addition, recently, anti-IL-5 mAb was shown to be beneficial in patients with hypereosinophilic syndrome [42, 43] and those with eosinophilic esophagitis [44, 45], re-affirming that the eosinophil represents a very important target cell for therapeutic intervention of diseases characterized by eosinophilia. …”
Section: Discussionmentioning
confidence: 99%
“…1,11,13 To investigate a potential role for syntenin in IL-5-driven eosinophilopoiesis, we cultured primary human cord blood-derived CD34 ϩ cells in the presence of IL-3 and IL-5 to induce eosinophil differentiation. In these cultures, syntenin was strongly up-regulated as indicated by Western blot analysis ( Figure 5A-B).…”
Section: Syntenin Is Critical For Eosinophil Differentiationmentioning
confidence: 99%
“…7-10 IL-5 specifically promotes eosinophil differentiation and survival from common myeloid progenitors, and plays a dominant role in the development of a subtype of B cells termed B1 cells. [11][12][13][14][15][16] Because the intracellular domains of IL-3R␣, GM-CSFR␣, and IL-5R␣ are unique, these are excellent candidates to mediate specific signaling pathways and cellular functions. We previously identified syntenin as specific interactor of intracellular IL-5R␣.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the blocking or depleting IL-5 from asthmatic patients will result in both allergic inflammation and symptom remission. In fact, a few lines of investigations have shown that passive administration of anti-IL-5 monoclonal antibodies or experimental vaccines against IL-5 not only inhibited recruitment of eosinophils from the bone marrow into the targeted organs, but also attenuated allergic inflammation and clinical symptoms (Menzies-Gow et al, 2003;Simon et al, 2005;Sutton et al, 2005).…”
Section: Introductionmentioning
confidence: 99%